#TITLE_ALTERNATIVE# - Diani Nur Muflihah ( NIM : 15713006 ), Astri
Cisarua Water Treatment Plant (WTP) is one of WTP managed by PDAM Tirta Raharja 4th branch, Padalarang. Up until now, the treatment capacity of this WTP is 38 l/s, and already stopped to offer a new house pipe installation due to its water production has reached its maximum consumers. House pipe connections that have been installed up until February, 2017 are 3,789 house pipe connections. In 2016-2017, there are 37 number of consumers in waiting list because PDAM stop to intstall new house pipe connections. In the other hand, 14% of population in Ngamprah Sub-district and Cisarua Sub-district, which are service areas of Cisarua WTP, can’t access improved drinking-water source. Therefore, to guarantee and control drinking water quality for those who can’t access improved drinking-water source, it is a need to uprate Cisarua WTP, Cisarua Sub-district, West Bandung Regency. Hopefully, this could increase productivity and health level in service areas. The design period of this detail engineering design will be 5 years and operational period starts from 2019. Population and water demand in that period of time are predicted by applying several population growth models, so the WTP capacity that needs to be increased is known. It is 120 l/s. The utilization of 120 l/s water from Cimahi River upstream is 13.6% of the total average flow rate of the river. It matches the regulation of maximum river utilization. Raw water from Cimahi River Upstream has a good quality. It meets the standard of raw water for drinking water, 3 of them don’t meet the standard of drinking water. Those parameters are turbidity, iron, and color. So, based on those parameters, the suitable configuration of technology could be decided. Based on the raw water quality, 3 treatment configurations were developed and by applying Analytical Hierarchy Process (AHP) method the 1st alternative was chosen. Every unit in this alternative was calculated its dimensions and fitted to available area (layouting). The result showed that the area needed for this new installation is 950 m2, and the existing land area can carry the required area without being enlarged. Investment cost to construct this WTP is about Rp19.6 billion